2021
DOI: 10.1017/cjn.2021.70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Parkinson’s Disease: a Single-Centered Qualitative Study

Abstract: Background: The public health measure restrictions across the world due to COVID-19 have inadvertently impacted the routines for people with Parkinson’s disease (PD) and their care partners not only in terms of compromised neurological clinical care but also drastically changing the way of life to minimize the risk of becoming infected. This study explores initial PD patients’ lived experiences to observe how quality of life and health care has been affected at the start of the COVID-19 pandemic and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 36 publications
3
35
1
Order By: Relevance
“…These disruptions extended to rehabilitative therapies; in one survey-based study, 60% of individuals with PD lost their access to rehabilitative care [12]. In a qualitative study, many individuals with PD reported feeling alone and unsupported during the pandemic due to limited communication with their providers [24]. Access to treatment was not uniformly disrupted.…”
Section: Impact Of the Pandemic On Individuals With Movement Disordersmentioning
confidence: 99%
“…These disruptions extended to rehabilitative therapies; in one survey-based study, 60% of individuals with PD lost their access to rehabilitative care [12]. In a qualitative study, many individuals with PD reported feeling alone and unsupported during the pandemic due to limited communication with their providers [24]. Access to treatment was not uniformly disrupted.…”
Section: Impact Of the Pandemic On Individuals With Movement Disordersmentioning
confidence: 99%
“…However, subjective worsening of motor and non-motor symptoms of uninfected PD patients during the time of the pandemic was also recorded in different studies [ 143 , 144 ]. New behavioral symptoms were observed in 26% of PD patients in an Italian cross-sectional study [ 144 ].…”
Section: Chaptermentioning
confidence: 99%
“…New behavioral symptoms were observed in 26% of PD patients in an Italian cross-sectional study [ 144 ]. PD patients reported feeling lonely and deprived of the support and communication with their physician [ 143 ].…”
Section: Chaptermentioning
confidence: 99%
“…During the global COVID‐19 pandemic, many governments gradually introduced national and local restrictions that impacted people's activities, health and well‐being. As a susceptible clinical group (Antonini et al, 2022 , 2020 ; Elbeddini et al, 2020 ), PwPD had to modify their care routines and the healthcare systems underwent changes in the ways clinicians and PwPD interacted in response to restrictions of the COVID‐19 pandemic (Thomas et al, 2020 , 2020 ). This meant that services that support Parkinson's care management had to cease or be delivered remotely.…”
Section: Introductionmentioning
confidence: 99%